Clinical characterization and prognostic implications of metabolic syndrome in patients undergoing peritoneal dialysis at a Chinese center. Issue 11 (November 2019) - Zhang, Rui-Ning; Hao, Hui-Fang; Zhang, Wei; Li, Qing; Ren, Li-Jie; Jia, Lan; Wei, Fang; Chen, Hai-Yan; Wang, Zhe; Bi, Xue-Qing; Pang, Hai-Yan; Jiang, Ai-Li; et al.
Objective: Metabolic syndrome (MS) is a common clinical condition associated with cardiovascular disease in patients undergoing peritoneal dialysis (PD); however, its prognostic implication among patients receiving PD remains controversial. Methods: In a prospective study from January 2013 and June 2016, we enrolled 190 patients undergoing PD and followed them for 46.4 ± 30.7 months. We assessed the associations of clinical characteristics and measurements with diabetes mellitus (DM) status, MS, and prognostic outcomes among the included patients. Results: We found that DM was associated with shortened duration of dialysis and poor survival. The prevalence of MS was 58.9% among all patients. We found significant differences in age, body weight, body mass index, triglycerides, high-density lipoprotein cholesterol, fasting plasma glucose, leukocytes, platelets, neutrophil percentage, and pre-albumin between patients with and without MS. We found a negative correlation trend between serum intact parathyroid hormone and MS among our patients. The arteriosclerosis index was significantly elevated in the MS group compared with the non-MS group. Serum calcium concentration and frequency of hospital admissions were significantly associated with mortality and technique failure. Conclusions: MS was positively associated with cardiovascular disease. DM, and hypocalcemia. Frequent hospital admissions can predict poor prognosis in patients undergoing PD.